Synthesis of new piperazine-oxadiazole derivatives and investigation of their anticancer activities - Uslu, Harun; Goktas, Bunyamin; Osmaniye, Derya; Levent, Serkan; Goktas, Sare Pece; Ozkan, Begum Nurpelin Saglik; Benkli, Kadriye (Elsevier, 2025)
Since cancer is one of the leading causes of human death, recent research has largely focused on developing multi-target drug designs. In this study, we designed and synthesized a series of piperazine-oxadiazole derivatives as aromatase inhibitors for the treatment of cancer. Their structures were confirmed by 1 H NMR, 13C C NMR, HRMS and FTIR spectroscopic methods. Cytotoxicity (MTT) was performed to determine the anticancer activity of the compounds as aromatase inhibitors against breast (MCF7), fibroblast (NIH3T3) and lung (A549) cell lines. Letrazol was used as the reference agent, compound 4b exhibited a significant effect among other derivatives with a value of IC50=2.103 +/- 0.088 50 =2.103 +/- 0.088 mu M against the MCF7 cell line. Docking study showed that 4b was one of the compounds with the best pose on the aromatase. The docking study showed that 4e was one of the compounds that gave the best pose on EGFR and topoisomerase. When the aromatase, EGFR and topoisomerase docking results were compared, it was concluded that our synthesized compounds may be more effective on the Aromatase macromolecule. From the obtained evaluations of the designed batches, compound 4b appeared to be a promising agent as an aromatase inhibitor for further research and evaluation studies in the future.
Keywords: Anticancer; Cytotoxcicity; Oxadiazole; Piperazine; Aromatase; Topoisomerase; EGFR